Ethanol sensing property of novel phthalocyanines substituted with 3,4-dihydroxy-3-cyclobuten-1,2-dione - Yazici, Aysegul; Dalbul, Nida; Altindal, Ahmet; Salih, Bekir; Bekaroglu, Ozer (ELSEVIER SCIENCE SA, 2014)
The novel mono metallo [Zn(II) 2a and Co(II) 2b] phthalocyanines have been synthesized from compound 1, which can be obtained by the reaction of 4-nitrophthalonitrile with 3,4-dihydroxy-3-cyclobuten-1,2-dione. The novel mono phthalocyanines with cyclobuten unit have been characterized by elemental analysis, UV-vis, FT-IR, H-1 NMR, and mass spectroscopy. The effect of humidity on the ethanol sensing capability of the spin coated lilms 2a and 2b has been studied. The results showed that the presence of humidity, acting as interference gas, reduces both sensitivity and response time of the sensors. In addition, studies on response time and repeatability of the sensors have also been carried out. Applications of Elovich and Ritchie kinetic models to adsorption systems were reviewed. Results show that while the Ritchie equation may be applied for low temperature adsorption processes, while Elovich equation generates a straight line that best fit to the data of adsorption of ethanol vapors on Pc films at higher temperature. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Ethanol sensing; Sensitivity; Sensing mechanism; DOUBLE-DECKER LU(III); HETERO-DINUCLEAR PHTHALOCYANINES; THIN-FILMS; ELECTROCHEMICAL PROPERTIES; ELECTRICAL-PROPERTIES; ZINC-PHTHALOCYANINE; ELOVICH EQUATION; HIGH-SENSITIVITY; METAL-FREE; BALL; Chemistry; Electrochemistry; Instruments & Instrumentation